Georgina García Gutiérrez, Los disfraces: la obra mestiza de Carlos Fuentes. 2a ed., El Colegio de México, México, 2000; 214 pp. - Corral Jorda, Rose (El Colegio de México, 2001)
Se reseñó el libro: Los disfraces: la obra mestiza de Carlos Fuentes. 2a ed